Developing a Pastry Product with Tropical Liquid Seaweed Eucheuma Cottonii - Macas, Lezyl; Cano, Jesszon; Gucor, May Amor; Olaso, Lilanie; Lim, Darwin (JPAIR Multidisciplinary Research, 2020)
Currently, our society lives under a deceptive apprehension of there being food abundance. Many humans are surrounded by using quick meals prosperous in calories and unsaturated fats, high-powered advertising, and over-consumption. The mass market has truly emerged as accustomed to the expression of junk food to designate such offerings, yet this incredibly processed food is bumped off in giant amounts. This study aimed to develop a pastry product with tropical liquid seaweed (Eucheuma Cottonii). The participants chose lot 2 with 10 grams of tropical liquid seaweeds according to their impression and judgment of the product in terms of appearance, chose lot 2 with 10 grams according to the product’s visual sensation, chose lot 1 with 5 grams according to the fineness and crunchiness of the product, chose lot 1 with 5 grams according to the degree of the flavor, terms of general acceptability the participants chose lot 1 with 5 grams as their preferred treatment and the ideal amount of tropical liquid seaweed in making pastry. Moreover, tropical liquid seaweed (Eucheuma Cottonii) is loaded with nutrients, especially different dietary fibers, and other nutrients. Furthermore, using tropical liquid seaweed in making white peanut cookies is ideal for the benefit of people in terms of health.
Keywords: Acceptability; product development; quasi-experimental; Bohol; Philippines